Large amplitude solitary waves in and near the Earth’s magnetosphere, magnetopause and bow shock: Polar and Cluster observations - C. Cattell; C. Neiman; J. Dombeck; J. Crumley; J. Wygant; C. A. Kletzing; W. K. Peterson; F. S. Mozer; M. André (Nonlinear Processes in Geophysics, 2003)
Solitary waves with large electric fields (up to 100's of mV/m) have been observed throughout the magnetosphere and in the bow shock. We discuss observations by Polar at high altitudes ( ~ 4-8 RE ), during crossings of the plasma sheet boundary and cusp, and new measurements by Polar at the equatorial magnetopause and by Cluster near the bow shock, in the cusp and at the plasma sheet boundary. We describe the results of a statistical study of electron solitary waves observed by Polar at high altitudes. The mean solitary wave duration was ~ 2 ms. The waves have velocities from ~ 1000 km/s to  > 2500 km/s. Observed scale sizes (parallel to the magnetic field) are on the order of 1-10lD, with eF/kTe from ~ 0.01 to O(1). The average speed of solitary waves at the plasma sheet boundary is faster than the average speed observed in the cusp and at cusp injections. The amplitude increases with both velocity and scale size. These observations are all consistent with the identification of the solitary waves as electron hole modes. We also report the discovery of solitary waves at the magnetopause, observed in Polar data obtained at the subsolar equatorial magnetopause. Both positive and negative potential structures have been observed with amplitudes up to ~ 25 mV/m. The velocities range from 150 km/s to >2500 km/s, with scale sizes the order of a kilometer (comparable to the Debye length). Initial observations of solitary waves by the four Cluster satellites are utilized to discuss the scale sizes and time variability of the regions where the solitary waves occur. Preliminary results from the four Cluster satellites have given a glimpse of the spatial and temporal variability of the occurrence of solitary waves and their association with other wave modes. In all the events studied, significant differences were observed in the waveforms observed simultaneously at the four locations separated by ~ 1000 km. When solitary waves were seen at one satellite, they were usually also seen at the other satellites within an interval of a few seconds. In association with an energetic electron injection and a highly compressed magnetosphere, Cluster has observed the largest amplitude solitary waves (>750 mV/m) ever reported in the outer magnetosphere.